Effect of Solid-State Fermentation on Nutritional Quality of Leaf Flour of the Drumstick Tree (Moringa oleifera Lam.) - Shi, Honghui; Yang, Endian; Li, Yun; Chen, Xiaoyang; Zhang, Junjie (Frontiers in Bioengineering and Biotechnology, 2021)
The drumstick tree is a fast-growing multipurpose tree with a large biomass and high nutritional value. However, it has rarely been exploited as a protein source. This study investigated solid-state fermentation induced by Aspergillus niger, Candida albicans and Bacillus subtilis to obtain high-quality protein feed from drumstick leaf flour. The results showed that fermentation induced significant changes in the nutritional composition of drumstick leaf flour. The concentrations of crude protein, small peptides and amino acids increased significantly after fermentation. The protein profile was also affected by the fermentation process. Macromolecular proteins in drumstick leaf flour were degraded, whereas other high molecular weight proteins were increased. However, the concentrations of crude fat, fiber, total sugar and reducing sugar were decreased, as were the anti-nutritional factors tannins, phytic acid and glucosinolates. After 24 h fermentation, the concentrations of total phenolics and flavonoids were increased. The antioxidant capacity was also significantly enhanced.